PENGARUH MODEL PEMBELAJARAN ARTIKULASI TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV - Parapat, Ruth Faith Lovita (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This research aims to determine the influence of the articulation learning model on the speaking skills of class IV students at SDN 101831 Bintang Meriah. The population in this study was all class IV students at SDN 101831 Bintang Meriah, totaling 40 people and divided into 2 classes, namely class IV-A and class IV-B, the entire population was also used as the research sample. This research is a type of Quasi-experimental research with a Pretest Posttest Nonequivalent Control Group Design. The instrument used is an oral action test instrument using speaking based on visual and sound stimuli. The data analysis technique in this research uses the t-test. The results of calculating data on students' speaking skills obtained t_count 11.72 > t_table 2.024, with a significance level of α 0.05. So Ha is accepted and Ho is rejected, which means that with the application of the articulation learning model, the speaking skills of fourth grade students at SDN 101831 Bintang Meriah are higher than those of fourth grade students who are taught using the lecture learning model. So it can be concluded that there is a significant influence of the articulation learning model on the speaking skills of class IV students at SDN 101831 Bintang Meriah.